2009
DOI: 10.1177/0883073809338328
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging and Ultrasound Injury in Preterm Infants With Seizures

Abstract: The utility of magnetic resonance imaging (MRI) as a universal screening tool in preterm infants has been contested; however, MR is increasingly used in investigation of neonatal seizures. We evaluated 236 infants <34 weeks gestation at birth. Seizures were documented according to clinical standard of care. Infants were imaged using MRI and head ultrasound during the neonatal period. A neuroradiologist and ultrasonologist performed detailed reviews of the images. Nine infants (3.8%) had clinical suspicion of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Glass et al . [15] in their study reported that 3.8% preterm neonates had clinical seizures. The cranial ultra sound was abnormal in all these infants and was accurate for detecting IVH.…”
Section: Discussionmentioning
confidence: 99%
“…Glass et al . [15] in their study reported that 3.8% preterm neonates had clinical seizures. The cranial ultra sound was abnormal in all these infants and was accurate for detecting IVH.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with HUS, MRI has much higher resolution for parenchymal injury (32-35), and, as such, is more likely to detect injury associated with seizures in both preterm and term neonates. In one small study of preterm neonates with seizures, MRI provided information that could be useful to guide management or parent counseling (36). Transport and imaging using MRI is safe for preterm neonates, though it requires expertise both in neonatal transport and MR interpretation (37).…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is accepted as the gold standard imaging modality. [12] However, Transfontanelle ultrasonography (US) should be performed in emergency cases where MRI is not immediately available. Infants should be monitored with continuous video EEG if possible.…”
Section: Non-epileptic Paroxysmal Movementsmentioning
confidence: 99%